Implementation of Violation of E-Tilang Regulations in the Analysis of Human Resources and Criminal Law Perspectives in Indonesia - Nining Yurista Prawitasari; Apri Aji Setyawan (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The fine process that has been carried out conventionally is expected to be able to reduce the level of traffic violations, whereas the conventional ticket system still uses a paper system in one of its implementations. A manual ticket system that uses blanks or ticket letters. When a traffic user is proven to have committed a mistake or violation, the police officer will take several actions in accordance with applicable regulations. At present, the National Police have innovated by carrying out e-tickets by monitoring ETLE cameras. The theory used is the theory of human resources and the theory of bureaucratic reform and law enforcement theory. The methodology used is a qualitative approach. In research, the results of this research are in the form of an understanding that e-tickets have caused many violations, whether this is due to human resources or in the application of a policy whether there is a lack of optimization in conducting socialization.